Influence of risk perception, preventive behavior, movement and environment on malaria infection in Lundu district, Sarawak, Malaysia (Medical Journal of Indonesia, 2007)
The incidence of malaria in Sarawak is among the highest in Malaysia despite its downward trend since 2002. This study was conducted to identify the dominant risk factors related to malaria infection. A case-control study was conducted in Lundu District, Sarawak. Cases were 96 indigenous malaria cases registered from January to September 2005 at Lundu District Health Office. Controls were selected among those who never contracted malaria originating from the same villages as cases. Cases and control were similarly distributed with respect to age, number of household and total household income per month. Cases were more likely than controls to report high risk occupation, opened eaves, ever had movement for those aged 50 years or over and car ownership. Older age, male, lower socioeconomic level and perception of fatality toward malaria increased risk to malaria infection. Male than female had seven-fold risk to be malaria infected [adjusted odds ratio (ORa) = 7.09; 95% confidence interval (CI) = 3.21-15.65]. In term of perception of fatality toward malaria, those who did not have than did have perception of fatality toward malaria had six-fold risk to be malaria infected (ORa = 6.38; 95% CI = 1.32-30.87). On contrary, those who had lower than middle and high per capita income per month had 85% lowered risk to be malaria infected (ORa = 0.15; 95% CI = 0.03-0.72). Male, older age, lower education and socioeconomy level, lower perception towards malaria, or lower environment sanitation had increased risk to be malaria infected. (Med J Indones 2007; 16:267-71)